STRESS OF ANGLE SECTION SUBJECTED TO TRANSVERSAL LOADING ACTING OUT OF THE SHEAR CENTER (Advances in Civil and Architectural Engineering, 2021)
Angle or L-section bars are commonly used as non-structural elements in modern buildings, such as carriers of massive and expensive glass walls. While they are commonly loaded with shear forces, they can nonetheless be subjected to significant torsion, which occurs from loading outside the shear center, and can be omitted. This omission may result in lack of shear bearing capacity. Shear and additional normal stresses were investigated due to torsion and without one. Analytical calculations in the linear-elastic domain showed a significant increase in shear stresses due to torsion. In addition, we compared the results with numerical models to test the accuracy of the analytical calculations and the suitability of numerical models.